Efficacy of Neem Seed Oil against the Babul Whitefly Acaudaleyrodes rachipora (Singh) (Aleyrodidae: Homoptera) - Sundararaj, R.; Murugesan, S.; Mishra, R. N. (Indian Forester, 1995)
An experiment was conducted to study the efficacy of neem seed oil and some conventional against the babul whitefly Acadaleyrodes rachipora on Acacia senegal. The results revealed that neem seed oil at 0.5, 0.3 and even at 0.1 % concentrations were very active and suppressed the development of the whitefly significantly while monocrotophos and endosulfan were not effective to suppress this whitefly.